Historic perspectives from anthropology. Reflections proposed to Transcultural Nursing - Cecilia Rohrbach Viadas (Universidad de Antioquia, 2015)
History brings together meanings related to earlier periods, being aware of the past as a panorama to reread the present. Madeleine Leininger presented in 1970 an implicit and respectful message to the Nursing Profession when introducing Nursing and Anthropology. Two Worlds to Blend. Implicitly: Nursing you disregard culture. This article shows the absence of the history of anthropology and of nursing within Transcultural Nursing and it includes how education has influenced theoretic, methodological, and comparative approaches giving researchers the responsibility to decide their fundamentals. Berthoud (2001) has inspired the anthropological and historic perspectives of the author, thus universalism, relativism, and comparison are presented.